Nutrient intake and stunting in children aged 2-5 years in a slum area of Jakarta - Ratnayani, Ratnayani; Sunardi, Diana; Fadilah, Fadilah; Hegar, Badriul (Paediatrica Indonesiana, 2024)
Background Stunting is one of the problems that occurs in children who live in slum areas. Inadequate nutrient intake has been associated with stunting in children. Objective To assess nutrient intake and analyze the differences between stunted and non-stunted children aged 2-5 years. Methods This comparative cross-sectional study compared nutrient intake and stunting among children 2-5 years in slum areas in Kebon Bawang Village North Jakarta. Subjects’ nutrient intake was assessed using the Semiquantitative-Food Frequency Questionnaire (SQ-FFQ). To analyze differences in subject characteristics and nutrient intake in the stunted and non-stunted groups, Chi-square, Mann-Whitney test, and independent T-test were used. Results From a total of 42 respondents, the characteristics of subjects were not significantly different between the stunted and non-stunted groups, in age (P=0.120), gender (P=0.126), maternal occupation (P=0.729), or maternal education (P=0.127). The stunted group had significantly lower intake of energy (P=0.003), carbohydrates (P=0.024), protein (P=0.005), and fat (P=0.001) than that of the non-stunted group. However, the majority of subjects had protein adequacy above the sufficiency level in both groups (P=0.638), while significantly more subjects in the stunted group had insufficient carbohydrate adequacy than in the non-stunted group (P=0.032). Conclusion Overall, nutrient intake in the stunted group is lower than that of the non-stunted group. Protein adequacy is above sufficient for most subjects in both groups, while the significantly more stunted subjects have insufficient carbohydrate adequacy. In carrying out interventions, it is necessary to consider fulfilling a balance of nutrients, especially macronutrients.